1992
DOI: 10.1182/blood.v80.11.2721.bloodjournal80112721
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-4 (IL-4) receptor expression on human T cells is affected by different intracellular signaling pathways and by IL-4 at transcriptional and posttranscriptional level

Abstract: Interleukin-4 (IL-4) modulates the survival, proliferation, and differentiation of a variety of hematopoietic cells. The effects are mediated through a single class of high-affinity receptors for IL-4. To understand the biologic effects of IL-4 on human T cells, we studied the regulation of IL-4 receptor (IL-4R) gene expression. We showed that IL-4R mRNA accumulation in human T cells is enhanced fourfold after activation of different secondary signaling pathways by concanavalin A (Con A), phorbol myristate ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…3a). Dokter et al have reported a similar effect of IL-4 on IL-4Ra mRNA expression in T cells [31]. This upregulation in receptor may have two effects-render the cells more responsive to IL-4 if expressed on the cell surface or less responsive if the receptor is secreted and sequesters IL-4.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…3a). Dokter et al have reported a similar effect of IL-4 on IL-4Ra mRNA expression in T cells [31]. This upregulation in receptor may have two effects-render the cells more responsive to IL-4 if expressed on the cell surface or less responsive if the receptor is secreted and sequesters IL-4.…”
Section: Discussionmentioning
confidence: 90%
“…IL-4 has been shown to upregulate gene expression of IL-4Ra [31], CCL22 [32], and IL-6 [33]. Several studies also showed that IL-4 treatment can reduce IL-6, IL-8, IL-12 mRNA, and protein levels in cells stimulated with inflammatory cytokines or proteins [34−38].…”
Section: Il-4 Treatment Affects the Regulation Of Downstream Genesmentioning
confidence: 99%
“…In particular, many other cell types, including those we observe in the inflamed state (Fig. 2 ), possess the IL-4Rα [ 45 49 ] and are therefore potential targets of receptor blockade. Future experiments will be necessary to determine the roles of other cell types in promoting Aβ clearance.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4Ra chain expression is regulated by different signalling pathways, including those activated by TCR and IL-4. 34 Upon activation, naive CD4 + T cells up-regulate IL-4Ra chain expression. Our data show that under Th2 polarizing conditions IL-4Ra chain is readily up-regulated and kept at high level during the stimulation period.…”
Section: Discussionmentioning
confidence: 99%
“…IL-4Ra chain expression is regulated by different signalling pathways, including those activated by TCR and IL-4 itself, that lead to its up-regulation during Th2 cell differentiation. 34 IL-4Ra chain expression was examined by Western blot in CD4 + T cells stimulated under Th2 polarizing conditions for 1-5 days. Results show that IL-4Ra chain expression is low in naive CD4 + T cells and increases after stimulation.…”
Section: Ctla-4 Engagement Inhibits Il-4ra Chain Expressionmentioning
confidence: 99%